Performance of soft clay stabilized with the replacement of palm oil fuel ash and gypsum - Abdulmajeed Ali Mohammed, Nasser Al-Hokabi (2022)
The worldwide population growth requires more means of life, accommodation, and food, which leads to people’s motion to the coastline or unstable weak soil areas. Malaysia as one of the main producers of palm oil is required to produce enough supplies to meet the palm oil global demand and maintain its gross national income. However, the generation of about 5 million tons annually of palm oil fuel ash waste have a harmful environmental impact. To tackle both issues, engineers adapted POFA waste upcycling to stabilize and enhance various geotechnical properties of clayey weak soil, kaolin as an example. This study is focusing on the effect of POFA and combined POFA-gypsum mixture on the performance of kaolin where gypsum is a pozzolan activator. Utilizing POFA as a stabilizing agent reduces environmental issues and waste landfill costs and enhances soft clays properties. Achieving Malaysian green technology goals requires an alternative method to balance economic growth and environmental privilege. This research proposes to investigate POFA and gypsum’s role in improving kaolin clay properties in terms of specific gravity, plasticity, compaction parameters, permeability, compressive, and shear strength with the curing period. Kaolin S300 is used as a control clay sample, POFA and gypsum as stabilizing agents. The optimum gypsum ratio is (4% and 6%) based on the previous literature, mixed as a binder with various POFA percentages (0,5,10, and 15). The results of treated samples show a clear drop of specific gravity with POFA-Gypsum addition, reduction of plasticity index, change of compaction characteristics parameters where optimum water content increased with a reduction in maximum dry density, variation in permeability and enhancement of compressive and shear strength with curing period and additives amount. Overall, POFA, gypsum and POFA-gypsum mixture enhanced the geotechnical properties of treated clay.